Salivary and hair cortisol as biomarkers of emotional and behavioral symptoms in 6–9 year old children - Golub, Yulia; Kuitunen-Paul, Sören; Panaseth, Kerstin; Stonawski, Valeska; Frey, Stefan; Steigleder, Ruth; Grimm, Jennifer; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kornhuber, Johannes; Kratz, Oliver; et al. (Physiology & behavior, 2019)
The aim of the present work is to investigate the association of salivary and cumulative cortisol levels with emotional and behavioral symptoms in a Franconian Cognition and Emotion Studies (FRANCES) general population cohort of 158 6- to 9 year old children. Salivary cortisol values were measured by one-day diurnal cortisol profile, whereas cumulative cortisol was estimated via one-month hair cortisol concentrations (rHCC). Nearly all significant associations of clinical symptoms with child cortisol indices were age dependent: We report emotional symptoms being associated with lower rHCC in younger children (6.06–7.54 years). In older children (7.55–9.41 years) behavioral problems were further associated with higher rHCC and lower salivary cortisol awakening responses. In summary, child clinical symptoms were stronger associated with markers of hair cortisol compared to salivary cortisol. To picture developmental mechanisms, we suggest longitudinal designs for cortisol measures of stress systems in children and adolescents.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Behavioral symptoms; Emotional symptoms; FRANCES; Hair cortisol; HPA axis; Salivary cortisol